TRAINING SANITATION HYGIENE SKILLS AND PRODUCTION MANAGEMENT OF "JAHE SEHAT" BEVERAGE IN AL HIDAYAH SENIOR HIGH SCHOOL STUDENTS, MOJOKERTO - Ah Yusuf; Rizki Fitryasari; Esti Yunitasari; Rr Dian Tristiana (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2021)
Most home and micro-scale industries have poor business management. Good management is able to produce the desired result or good in the business being run. The partner in this community service activity is students of Al Hidayah Senior High School in Mojokerto, who has a business in making ginger drinks “Jahe Sehat”. This training aimed to increase partner’s knowledge and skill about sanitation hygiene and production management. The manufacturing process starts from the preparation of raw materials, namely ginger, extraction, cooking, sieving, packaging and labeling to marketing. It was found that healthy ginger producers still do not understand the importance of hygiene and sanitation in the production process, unattractive packaging designs and no good financial cash planning system. The community service team conducts training and outreach to solve the partner's problems. By carrying out this service activity, partners increase partner’ skills and knowledge and the healthy ginger product "jahe sehat al-hidayah" has an attractive packaging.